Search for TeV-Scale Neutrino Dimuon Events with 10.7 Years of IceCube Data ... - Sarkar, Sourav (University of Alberta Library, 2023)
The IceCube neutrino observatory is a gigaton Cherenkov detector located at the geographic south pole. The experiment is designed to detect neutrinos originating from the atmosphere and astrophysical objects over a huge energy range from 10 GeV to 10 PeV. Information about the interacting neutrinos is extracted from the event reconstructions and identification of the event topologies, constituting probes to study high-energy particle physics and astrophysics. Typically, muon neutrinos produce a single muon from their interactions in ice via deep inelastic scattering (DIS) processes. However, in some fraction of the cases, the Standard Model predicts the production of two closely spaced high energy muons from the same neutrino interaction, referred to as dimuon. Detection of these events in IceCube can be a powerful tool to study rare standard model neutrino interactions and search for physics beyond the Standard Model at an energy scale beyond the reach of current accelerator neutrino experiments. However, ...